The Impact of Lecture Attendance on Exams for Novice Programming Students - Ashok Kumar Veerasamy; Daryl D'Souza; Rolf Lindén; Erkki Kaila; Mikko-Jussi Laakso; Tapio Salakoski (MECS Publisher, 2022)
In this paper, the correlation between lecture attendance and assessment tasks on final exam performance of introductory programming students has been analyzed to identify if lecture attendance, and completion of in-class and take home formative assessment tasks affects student performance in the final examination. In this study, only lecture attendance, homework exercises and class demonstration scores, and final exam marks have been considered. This study used Spearman's Rank correlation coefficient and multiple regression techniques via SPSS software to analyze the student data of the academic years 2012, 2013 and 2014 of an introductory programming course to test the hypotheses. It is found that, there is a significant correlation between homework exercises and final exam scores. However, formal lecture attendance and final exam performance were negatively correlated. Moreover, multiple regression results of assessment tasks such as homework exercises, class activities and lecture attendance on final exam scores, did not provide any significant value to support the statement "Marks achieved in homework, class demonstrations, and lecture attendance, have a significant positive impact on final examination results".